Type-II Backlund transformations via gauge transformations - Aguirre, A. R. [UNESP]; Araujo, T. R. [UNESP]; Gomes, J. F. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Springer, 2011)
The construction of type II Backlund transformation for the sine-Gordon and the Tzitzeica-Bullough-Dodd models are obtained from gauge transformation. An infinite number of conserved quantities are constructed from the defect matrices. This guarantees that the introduction of type II defects for these models does not spoil their integrability. In particular, modified energy and momentum are derived and compared with those presented in recent literature.
Keywords: Integrable Equations in Physics; Integrable Field Theories